Persepsi Masyarakat terhadap Serangan Fajar dalam Pemilu 2024 - Jihan Zahira Nurista; Geni Novella; Muhammad Ikhwanurrahim; Salma Syakira (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study examines public perceptions of the practice of "dawn attack" in the 2024 election, which is a form of money politics that is still rampant in Indonesia. This study aims to understand how the public assesses the impact of such practices on democratic integrity and voter behavior. This study involved 101 respondents with diverse backgrounds, the majority of whom were students, and some came from other professions such as civil servants, teachers, entrepreneurs, and medical personnel. Data collection was carried out through an open questionnaire, which was then analyzed using thematic methods to identify the main patterns in the community's view. The results of the study showed that the majority of respondents considered the dawn attack as a form of political manipulation that undermined the principle of fairness in elections. As many as 56.4% of respondents admitted that they had seen or knew of this practice, with the main impact in the form of temporary economic benefits and changes in voter behavior. This study highlights the importance of concrete steps in suppressing the practice of money politics, including through stricter law enforcement and political education for the public. Thus, this research is expected to contribute to efforts to create a fairer, more transparent, and democratic electoral system in the future.